Evaluating group housing strategies for the ex-situ conservation of harlequin frogs (Atelopus spp.) using behavioral and physiological indicators - Cikanek, Shawna J.; Nockold, Simon; Brown, Janine L.; Carpenter, James W.; Estrada, Angie; Guerrel, Jorge; Hope, Katharine; Ibáñez, Roberto; Putman, Sarah B.; Gratwicke, Brian (My University, 2014)
We have established ex situ assurance colonies of two endangered Panamanian harlequin frogs, Atelopus certus and Atelopus glyphus, but observed that males fought with each other when housed as a group. Housing frogs individually eliminated this problem, but created space constraints. To evaluate the potential stress effects from aggressive interactions when grouping frogs, we housed male frogs in replicated groups of one, two, and eight. We measured aggressive behavioral interactions and fecal glucocorticoid metabolite (GC) concentrations as indicators of stress in each tank. In both small and large groups, frogs initially interacted aggressively, but aggressive interactions and fecal GCs declined significantly after the first 2 weeks of being housed together, reaching the lowest levels by week 4. We conclude that aggressive interactions in same-sex groups of captive Atelopus may initially cause stress, but the frogs become habituated within a few weeks and they can safely be housed in same-sex groups for longer periods of time.
Keywords: Panamanian harlequin frogs; Group housing; Ex-situ assurance colonies; Harlequin frogs; Atelopus; Conservation